Analisis Strategi Humas Diskominfo Kota Bogor dalam Mengelola Media Sosial Instagram @Kominfobogor - Ratu Rania; Anisa Diniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the public relations strategy of the Bogor City Communication and Information Service in managing social media Instagram @kominfobogor and also the public's response to the public relations activities of the Bogor City Communication and Information Service in managing social media Instagram @kominfobogor. The method used by researchers is a qualitative approach through interviews with the target informants. The object that is focused on in this study is the Bogor Information and Communication Service. The results show that the application of the public relations strategy by the Bogor City Diskominfo still has several shortcomings, such as planning that is not optimal when brainstorming is carried out, not having a certain time to post content, content and packaging forms that are too monotonous, to evaluation forms that can be further detailed. The conclusion of the research is the role of Diskominfo Bogor as public relations capable of managing social media content well. Actions taken are setting target audiences, creating timetables, and distributing content. Keywords: Content, Public Relations Strategy, Social Media